Analisa Kenyamanan Termal pada Ruang Belajar Fakultas Teknik Universitas Almuslim dengan Metode CBE Thermal Comfort Tool - Zuraihan, Zuraihan; Azizah, Cut; Yanis, Muhammad (Jurnal Sains Riset, 2024)
The thermal comfort in the study room affects the student's concentration. Measurement with 5 in 1 Environment Meters and CBE Thermal Comfort Tools analysis using the Adaptive Method for thermal comfort in open spaces with natural ventilation. This research uses a quantitative method with descriptive and evaluative methods. Analysis of measurement data and SNI as well as simulation using the CBE Thermal Comfort Tool application. Results Measurement of temperature in the room 28.7oC - 33.6oC. exceeds the maximum standard for comfortable heat category with an effective temperature of 25.8oC - 27.1oC. Simulation of CBE Thermal Comfort Tools The movement speed of air from the fan (ventilator) 0.8 m/s and 1.2 m/s, can create comfort in a room at 08.00–10.00 with a comfortable category at a temperature of 27oC–30oC. at 11.00 – 17.00 the room temperature increases 3-4oC, the room category becomes too warm. The comfort of the classroom can be achieved by adding 60% relative humidity with an air movement of 0.8 m/s.